Menakar Keadilan Sanksi Penjara dalam Perkara Pembunuhan Secara Bersama-Sama Menurut Pasal 338 Jo Pasal 55 KUHP - Ardyanto Tajuddin; Johamran Prasisto; Andi Mardaya; Amanda Dealova; Mila Khaerunnisa; Husnul Hatima (Jurnal Litigasi Amsir, 2025)
This study examines the application of criminal law to the offense of joint murder, using the District Court of Parepare Decision Number 111/Pid.B/2020/PN.Pre as a case study. It explores how the panel of judges constructs their legal reasoning by connecting the facts established at trial, including witness testimonies, forensic evidence, and material exhibits, with the relevant provisions of the Indonesian Criminal Code, particularly Article 338 in conjunction with Article 55 paragraph (1) sub-paragraph 1. The research employs a normative legal method with a statute approach and case approach, relying on primary legislation (the Criminal Code and the Code of Criminal Procedure), court decisions, and scholarly literature on offenses against life and doctrines of criminal liability as its main sources of legal material.